Analysis of the Application of Punishment to Employee Performance on the UTM Faculty of Medicine Construction Project - Eva Fauziyah; Soraya Dwi Valentina; Moh. Wahyu Fajri Ramadhan; Iriani Ismail (International Journal of Economics and Management Research, 2025)
This study aims to analyze the implementation of punishment on employee performance in the construction project of the Faculty of Medicine at the University of Trunojoyo Madura (UTM). In the context of human resource management, punishment is applied as a means of controlling deviant work behavior to achieve optimal discipline and productivity. This research employed a descriptive qualitative approach, using data collection techniques such as in-depth interviews and direct observation. The results indicate that the implementation of punishment executed in stages, fairly, and transparently, from verbal warnings to dismissal can encourage positive behavioral changes, increase employee responsibility, and strengthen adherence to safety standards. Thus, when applied in an educational and humane manner, punishment plays a crucial role in improving employee performance.